Over-the-air aided precoding for DL massive MIMO with distributed antenna sites - Aulin, Jocelyn (2016 10th European Conference on Antennas and Propagation (EuCAP), 2016)
We consider downlink (DL) transmission for a Time Division Duplex (TDD) LTE base station in a target cell with centralized baseband processing for a distributed Massive MIMO antenna system. The remote antenna units of the base station, distributed geographically within the target cell, also supports baseband processing complementing the centralized baseband unit. For DL data transmission, two-stage linear precoding, is used. The outer precoder is selected as the conjugate transpose of the effective downlink channel matrix, and has a distributed implementation across remote antenna sites, with final precoding achieved "over-the-air" via the linear superposition of the transmitted signals. The inner block diagonal precoder is derived by maximizing independently, the downlink achievable rate for each user. Significant gains in spectral efficiency results are obtained for two-stage precoding relative to single-stage precoding and for two-antenna sites relative to single-antenna site.